Efficiency and technical analysis of the Turkish National Team in 2017 Women`s European Volleyball Championship - Yapici, A.; Solmaz, Ö. (International Journal of Human Sciences, 2018)
In this study investigates how well Turkish National Team do in the 2017 Women`s European Volleyball Championship play up to their potential. To compare the potentials of the teams at the end of the championship and to determine the extent to which they reflect their current potential to this ranking. It is also possible to compare the ranking of the teams at the end of the championship with the data envelopment analysis and determine how much they reflect their current potential to this ranking. For the technical analysis of the Turkish National Team and their competitors in the 2017 Women's European Volleyball Championships, the scoreboard method was used for 21 matches. For efficiency analysis, data of 36 matches were calculated using data envelopment analysis. The data obtained for the efficiency analysis were separated as service, headline, attack and block and taken from the European Volleyball Confederation (CEV). The obtained results in Serbia, Netherlands, Turkey and Azerbaijan among the most rated teams is seen. Besides, it was seen that the ranking in the championship and super efficiency score ranking not the same. The Turkish national team completed the tournament as a third place may be due to the high performance difference in the field compared to the other teams. As a result, the results obtained from the data envelopment analysis with this study are important because it will enable them to determine their targets in the following seasons over the current potential of the team.